Network Analysis Reveals a Role for Salicylic Acid Pathway Components in Shade Avoidance. Issue 4 (22nd October 2018) - Nozue, Kazunari; Devisetty, Upendra Kumar; Lekkala, Saradadevi; Mueller-Moulé, Patricia; Bak, Aurélie; Casteel, Clare L.; Maloof, Julin N.
Abstract : Shade avoidance involves complex regulation of multiple hormone network modules, and salicylic acid pathway genes are required for petiole shade avoidance. Abstract: Plants have sophisticated mechanisms for sensing neighbor shade. To maximize their ability to compete for light, plants respond to shade through enhanced elongation and physiological changes. The shade avoidance response affects many different organs and growth stages, yet the signaling pathways underlying this response have mostly been studied in seedlings. We assayed transcriptome changes in response to shade across a 2-d time course in the wild type and 12 Arabidopsis ( Arabidopsis thaliana ) mutants. The resulting temporal map of transcriptional responses to shade defines early and late responses in adult plants, enabling us to determine connections between key signaling genes and downstream responses. We found a pervasive and unexpectedly strong connection between shade avoidance and genes related to salicylic acid, suggesting salicylic acid signaling to be an important shade avoidance growth regulator. We tested this connection and found that several mutants disrupting salicylic acid levels or signaling were defective in shade avoidance. The effect of these mutations on shade avoidance was specific to petiole elongation; neither hypocotyl nor flowering time responses were altered, thereby defining important stage-specific differences in the downstream shade avoidance signaling pathway. Shade treatment did not change salicylic acid levels, indicating that the mediation of shade avoidance by salicylic acid is not dependent on the modulation of salicylic acid levels. These results demonstrate that salicylic acid pathway genes also are key components of petiole shade avoidance.